Crimean Tatars in the Trade Union movement of the Crimean ASSR in the 1920–1930s - Grigorii Kondratjuk (Крымское историческое обозрение)
Research objectives: consider the activities of the Trade Unions of the Crimean ASSR in the interwar period in the context of national policy. Research materials: authentic editions of the 1920–30s, documents of the State Archive of the Republic of Crimea. Results and novelty of the research: the national policy of the Crimean ASSR was carried out, among other things, through the activities of the Crimean Council of Trade Unions (KSPS), which was an intermediary between the national peasantry and the VKPB. The korenization policy made changes to the KSPS itself, introducing a certain percentage of Crimean Tatars and representatives of other peoples into its structure. Trade unions have made a significant contribution to the eradication of illiteracy, school construction, and vocational education.